(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The world is facing a big challenge of antimicrobial resistance (AMR). Herbs have tremendous potential of antimicrobial activities. This study was aimed to find out the antimicrobial activity of aqueous ethanol extracts of Curcuma longa (CL) and Withania somnifera (WS) individually and in different ratios of formulations. Materials and methods: Herbs CL and WS were extracted in a predefined ratio of aqueous ethanol medium, condensed and the formulations were prepared in 25:75, 50:50 and 75:25 ratios respectively. Culture mediums of Bacillus subtilis and Serratia marcescens were prepared. A disc with the samples CL, WS, 25:75, 50:50 and 75:25 were placed in the cultured plate. The inhibition of microbial growth around the discs indicated the zone of inhibition. The presence or absence zone of inhibition was noted and its diameter was calculated. Results: CL did not show any antimicrobial activity against Bacillus subtilis individually. However, when combined with WS, it showed a significant effect. WS showed maximum effect against Bacillus subtilis, followed by 25:75, 50:50 and 75:25. İn case of Serrata marcescens, 25:75 showed maximum effect, followed by 75:25. Other extracts showed almost similar effect. Conclusion: CL and WS and their formulations have significant antimicrobial effect against Serratia marcescens. WS alone and in formulation with CL showed antimicrobial effect against Bacillus subtilis, but not CL. Formulation 25:75 showed better effect than other samples.